Spain’s Foreign Policy Toward Legal Immigrant - Muhammad Fauzan al ammari (MIHI UMY, 2016)
Abstrac — This abstrac is the core of the research that has been made by the writer to review the foreign policy of Spain toward immigrant. The policy that has been made by the government of Spain aim to control the flow of the immigration to come in and come out from Spain. This research aim to knowing the reason behind the process. The writer do the direct research in Spain to collecting data and also interview in the immigrants in Spain. For the research method its self, writer using qualitative and analysis method, by this research, writer give the facts that help to gain the conclusion. The result of research show the background of strong Spain history and the factors of Spain geography that help to made the policies.